Modelling the Monetary Multiplier and the Controllability of the Divisia Monetary Quantity Aggregates - Spindt, Paul A. (The Review of Economics and Statistics, 1984)
Fama, Eugene, and Richard Roll, Some Properties of Symmetric Stable Distributions, Journal of the American Statistical Association 63 (Sept. 1968), 817-838. ______ Parameter Estimates for Symmetric Stable Distributions, Journal of the American Statistical Association 66 (June 1971), 331-338. Friedman, Daniel, and Stoddard Vandersteel, Short-run Fluctuations in Foreign Exchange Rates: Evidence from the Data 1973-79, Journal of International Economics 13 (Aug. 1982), 171-186. Gnedenko, B. V., and A. N. Kolmogorov, Limit Distributions for Sums of Independent Random Variables (Reading, MA: Addison-Wesley, 1968). International Monetary Fund, International Monetary Fund Survev, various issues. Judge, George G., William E. Griffiths, R. Carter Hill, and Tsoung-Chao Lee, Theory and Practice of Econometrics (New York: John Wiley and Sons, 1980). Kendall, Maurice G., and Alan Stuart, Advanced Theory of Statistics, 2nd Edition, Vol. I (London: Charles Griffin and Co., 1963). Kindleberger, C. P., The Benefits of International Money, Journal of International Economics 2 (Sept. 1972), 425-442. Mandelbrot, Benoit, Variation of Certain Speculative Prices, Journal of Business 36 (Oct. 1963), 394-419. McFarland, James W., R. Richardson Pettit, and Sam K. Sung, The Distribution of Foreign Exchange Price Changes: Trading Day Effects and Risk Measurement, Journal of Finance 37 (June 1982), 693-715. Moulton (Westerfield), Janice, An Estimation of Foreign Exchange Risk Under Fixed and Floating Rate Regimes, Journal of International Economics 7 (June 1977), 181-200. Rogalski, Richard J., and Joseph D. Vinso, Empirical Properties of Foreign Exchange Rates, Journal of International Business Studies 9 (Fall 1978), 69-79. Roll, Richard, Behavior of Interest Rates (New York: Basic Books, Inc., 1970). Schmidt, Peter, Econometrics (New York: Marcell Dekker, Inc., 1976).